E-Commerce: Marketing Gift Fruit on the Internet - Robert L. Degner; Kimberly L. Morgan (EDIS, 2004)
There are two objectives of this paper: (1) to examine and critique the current Internet marketing practices of gift fruit shippers, and (2) to provide suggestions for improved Internet marketing efforts. This is EDIS document FE430, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published February 2004. This is an abridged version of the original document published in 2000.